La programación infantil en las radios católicas del sistema de comunicación franciscano de la ciudad de Quito y su incidencia como producto comunicacional educativo y de entretenimiento, en los estudiantes de educación básica del colegio franciscano San Andrés en la parroquia del centro histórico del Distrito Metropolitano de Quito, durante el período de febrero a julio de 2012 - Galindo Suárez, Mónica Cecilia (2014)
The present investigation was about "Children's programming on Franciscan Catholic Radio Communication System Quito and its incidence and communication product education and entertainment, in Basic Education Students ―San Andrés‖ Franciscan school District Historical Center of Quito, during the period from February to July 2012‖. It was structured and developed in accordance with the regulations in force graduation from the National University of Loja. The general objective was formulated: Promote the need and importance of incorporating in programming radio stations Franciscan Communication System, producing a Child Education Program, which contribute to strengthening their knowledge of public, educational and fun communications incidence in a context within the mission of the Franciscan Order. The methods used were: the inductive method and analytic - synthetic and statistician, the techniques and instruments used were: a survey of elementary school students from the San Andres Educational school for aspects of their affinity to the radial media Franciscan communication system and their preferences in radio programming. It was verified that 100% of students have an affinity with radio programming broadcast stations Franciscan communication system, accepting his radio pleased to participate in a live, considering that their participation is critical to develop their ability to communication and development in a media that reaches an audience radial unimaginable. Accordingly, it is determined that a child educational radio program can contribute successfully in the development of knowledge, skills and abilities in the students of ―San Andrés‖ school